2019
DOI: 10.1590/1678-7757-2018-0600
|View full text |Cite
|
Sign up to set email alerts
|

Impact of immediately loaded implant-supported maxillary full-arch dental prostheses: a systematic review

Abstract: Impact of immediately loaded implant-supported maxillary fullarch dental prostheses: a systematic review The immediate loading of implant-assisted fixed prostheses in edentulous maxillae may achieve favorable success rates with reduced treatment time. An evidence summary of clinical trials is key to recommend loading protocols in these cases. Objectives: To compare immediately loaded, fully implantsupported complete dentures to early and conventional/delayed loading in the edentulous maxillae of adult patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
(22 reference statements)
1
4
0
3
Order By: Relevance
“…The present study found no significant difference between the IL and DL groups regarding implant survival rate, with 99.2% and 97.9%, respectively. The results corroborate with the previously found by other authors but with smaller samples, with survival rates ranging from 93.9% to 100% for immediate loading and between 95.9% and 99% for delayed loading [7,16,17].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study found no significant difference between the IL and DL groups regarding implant survival rate, with 99.2% and 97.9%, respectively. The results corroborate with the previously found by other authors but with smaller samples, with survival rates ranging from 93.9% to 100% for immediate loading and between 95.9% and 99% for delayed loading [7,16,17].…”
Section: Discussionsupporting
confidence: 92%
“…Considering that no significant differences were found in implant and prosthesis survival rates between loading protocols, IL seems to be an effective alternative for full-arch rehabilitation, with predictable results in the long-term. This protocol involves a shorter treatment time, which is essential in achieving patient satisfaction [7]. Nevertheless, since retrospective studies may have some limitations that cannot be entirely overcome, such as limited and less accurate data, further prospective studies are needed to confirm the presented outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sobre a imediaticidade da reabilitação, a literatura mostra que independente do momento em que recebem um tratamento protético reabiltiador fixo, os pacientes ficam mais satisfeitos do que com trabalhos removíveis. A satisfação parece varias também de acordo com o momento do tratamento em que esse quesito é questionado e de acordo com a experência pregressa do paciente com próteses totais (ABDUNABI, et al 2019).…”
Section: Discussionunclassified